Microglia proliferation plays distinct roles in acquired epilepsy depending on disease stages. (15th June 2021) - Di Nunzio, Martina; Di Sapia, Rossella; Sorrentino, Diletta; Kebede, Valentina; Cerovic, Milica; Gullotta, Giorgia S.; Bacigaluppi, Marco; Audinat, Etienne; Marchi, Nicola; Ravizza, Teresa; Vezzani, Annamaria
Abstract: Objective: Microgliosis occurs in animal models of acquired epilepsy and in patients. It includes cell proliferation that is associated with seizure frequency and decreased neuronal cells in human epilepsy. The role of microglia proliferation in the development of acquired epilepsy is unknown; thus, we examined its contribution to spontaneous seizure, neurodegeneration, and cognitive deficits in different disease phases. Methods: We used a model of acquired epilepsy triggered by intra‐amygdala kainic acid in C57BL6N adult male mice. Mice were electroencephalographically (EEG) monitored (24/7) during status epilepticus and in early and chronic disease. Microglia proliferation was blocked by GW2580, a selective CSF1 receptor inhibitor, supplemented in the diet for 21 days from status epilepticus onset. Then, mice were returned to placebo diet until experiment completion. Control mice were exposed to status epilepticus and fed with placebo diet. Experimental mice were tested in the novel object recognition test (NORT) and in Barnes maze, and compared to control and sham mice. At the end of the behavioral test, mice were killed for brain histopathological analysis. Additionally, seizure baseline was monitored in chronic epileptic mice, then mice were fed for 14 days with GW2580 or placebo diet under 24/7 EEG recording. Results: GW2580 prevented microglia proliferation in mice undergoing epilepsy, whereas it did not affect microglia or basal excitatory neurotransmission in the hippocampus of naive mice. Mice with occluded microglia proliferation during early disease development underwent status epilepticus and subsequent epilepsy similar to placebo diet mice, and were similarly impaired in NORT, with improvement in Barnes maze. GW2580‐treated mice displayed neuroprotection in the hippocampus. In contrast, blockade of microglia proliferation in chronic epileptic mice resulted in spontaneous seizure reduction versus placebo mice. Significance: Microglia proliferation during early disease contributes to neurodegeneration, whereas in late chronic disease it contributes to seizures. Timely pharmacological interference with microglia proliferation may offer a potential target for improving disease outcomes.